Characterization of Disabilities Among Young Farmers in Uganda - David Agole; Connie D Baggett; Mark A Brennan; Aaron J McKim; Amanda Crump; Eriya B. Kule (Journal of International Agricultural and Extension Education, 2024)
It is essential for Agricultural and Extension Educators to understand the challenges facing all the individuals they serve; therefore, this study examined the characteristics of young farmers with disabilities in Northern and Eastern Uganda. The objectives were to determine disability demographics and the relationship between major causes of disability by type and age. The study used a comparative- cross-sectional research design involving 388 young farmers with disabilities in Uganda. The sample selection strategies involved the use of a stratified, random and criterion purposive sampling techniques. Descriptive statistics and chi square tests were used in analysing data. The findings indicated many young farmers with disabilities are male, 20 to 29 years old, married, and attained a primary school education. Most households had at least one person with a disability. Many young farmers have an innate disability and experience moderate to severe limitations in daily life activities. Most disabilities were linked with loss of limbs among those aged 20 to 29 years. However, there were statistically significant associations between the types of disabilities among young farmers across the various age categories. Disability statistics could guide interventions for minimizing disability rates and provisions for assistive devices for individuals with disabilities.
Keywords: Agriculture; disability; inclusive education; Uganda; young farmers